Penentuan Kondisi Optimum Desorpsi Anion Nitrat (NO3-) pada Silika Mesopori Termodifikasi Dimetilamina (DMA) - Dipnorita Retno; Budhi Oktavia; Indang Dewata; Miftahul Khair (Periodic, 2023)
Mesoporous silica is an inorganic materials that has high potential to be applied in various industrial fields, one of its application is the adsorption method. To maximize the adsorption of mesoporous silica, modification of the silica surface was carried out with the addition of amine compounds. The amine compound used as a modifier is dimethylamine (DMA). Mesoporous silica which has been modified with dimethylamine is used in the nitrate anions adsorption process by the column method. The adsorption capacity of the nitrate anion is 0.0917 mg/g. After being adsorbed, the desorption process was carried out to release the adsorbed nitrate anions again. From the desorption process, it was found that HCl proved to be the best desorption agent used on nitrate anions. The optimum concentration of HCl was 0.15 M with the number ofÂ  nitrate anions desorbed as much as 0.0459 mg with a 100% desorption percentage.